The Bacterial and Fungal Microbiota of Nelore Steers Is Dynamic Across the Gastrointestinal Tract and Its Fecal-Associated Microbiota Is Correlated to Feed Efficiency - Lopes, Déborah Romaskevis Gomes; La Reau, Alex J.; Duarte, Márcio de Souza; Detmann, Edenio; Bento, Cláudia Braga Pereira; Mercadante, Maria Eugênia Zerlotti; Bonilha, Sarah Figueiredo Martins; Suen, Garret; Mantovani, Hilario Cuquetto (Frontiers in Microbiology, 2019)
The ruminant gastrointestinal tract (GIT) microbiome plays a major role in the health, physiology and production traits of the host. In this work, we characterized the bacterial and fungal microbiota of the rumen, small intestine, cecum and feces of 27 Nelore steers using next-generation sequencing and correlated them with biochemical parameters within the GIT segments. We found that only the bacterial microbiota clustered according to each GIT segment. Bacterial diversity and richness as well as volatile fatty acid concentration was lowest in the small intestine. Taxonomic grouping of bacterial operational taxonomic units (OTUs) revealed that Lachnospiraceae (24.61 ± SD 6.58 %) and Ruminococcaceae (20.87 ± SD 4.22 %) were the two most abundant taxa across the GIT. For the fungi, the family Neocallismastigaceae dominated in all GIT segments, with the genus Orpinomyces being the most abundant. Twenty-eight bacterial and six fungal OTUs were shared across all GIT segments in at least 50% of the steers. We also evaluated if the fecal-associated microbiota of steers showing negative and positive residual feed intake (n-RFI and p-RFI, respectively) was associated with their feed efficiency phenotype. Diversity indices for both bacterial and fungal fecal microbiota did not vary between the two feed efficiency groups. Differences in the fecal bacterial composition between high and low feed efficiency steers were primarily assigned to OTUs belonging to the families Lachnospiraceae and Ruminococcaceae and to the genus Prevotella. The fungal OTUs shared across the GIT did not vary between feed efficiency groups, but 7 and 3 OTUs were found only in steers with positive and negative RFI, respectively. These results provide further insights into the composition of the Nelore GIT microbiota, which could have implications for improving animal health and productivity. Our findings also reveal differences in fecal-associated bacterial OTUs between steers from different feed efficiency groups, suggesting that fecal sampling may represent a non-invasive strategy to link the bovine microbiota with productivity phenotypes.